Digital libraries - creating information space excellence: is it already time for benchmarking? - Vrana, Radovan (2002)
As they are gradually becoming mature, digital libraries are being put more frequently under a magnifying glass in order to be evaluated. Some of the world's leading information scientist like T. Saracevic (Rutgers University, USA) claim that it is too early to evaluate quality of existing digital libraries as they are not yet taken their final shape and there is much to be expected from such young and important information institutions. The idea of evaluation of services of digital libraries has come from scientists and professionals measuring quality of the existing library services. Some scientists also consider problem of persistence of digital libraries an their information sources as a prerequisite for design of evaluation tools for measuring various aspects of digital library services. Literature review in this field also shows major concerns for comparison of digital library content representation and categorization, advanced tools and processes in traditional libraries and their counterparts in digital libraries. Aim of this paper is to give a view of current perspectives in this area.
Projekt MZOS
ENG